Factors Determining Stress of Street Children in Gresik Regency During the Covid-19 Pandemic - Istiadji, Erdi; Nurlailyc, Novalia (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2024)
Street children phenomenon in Indonesia is a complex problem in terms of physical, psychological, and social aspects. The results of the preliminary study showed that Gresik Regency was one of the regencies in East Java that experienced an increase in the number of street children during the Covid-19 pandemic. Street children have different backgrounds and have experienced various pressures and threats as stressors that make them stressed. This study aims to analyze stressors or factors that determinating stress in street children in Gresik Regency during the Covid-19 pandemic. Methods : This research method is qualitative with a phenomenological approach. Determination of informants using snowball technique. Data were collected using in-depth interviews, observation, and documentation. Data analysis used interactive analysis and credibility was verified using triangulation of sources and techniques. Result : Stressors for street children in Gresik Regency during the Covid-19 pandemic are rarely talking to parents, exploitation by parents, bullying at school, the implementation of the PSBB policy, the increasing number of street children, policing by Satpol-PP officers, extortion of money by thugs or more mature buskers, and busking results that do not reach the target. Conclusion : Factors determining the stress of street children in Gresik Regency during the Covid-19 pandemic are the family environment, social environment, and threats they get on the streets.